Diseño de un laboratorio virtual para la enseñanza del cálculo de pérdidas de presión en tuberías para la UAN Sede Neiva - Cumaco Olarte, Juan Camilo; Cumaco Pascuas, Carlos Alberto (Universidad Antonio Nariño, 2021)
Laboratory practice is a powerful pedagogical strategy for the construction of procedural competencies and for this reason it is used in a great variety of academic programs, usually synchronized with its corresponding theoretical subject. Virtual laboratories stand out for their visual impact and animation characteristics, which simulate the environment of a real laboratory. In this work, the design of a virtual laboratory for teaching the calculation of pressure losses in pipes is presented using air as a working substance, an aspect that is absent in the current study programs of the UAN. The virtual modeling of the different components is carried out in the SOLIDWORKS software, in which each of the elements that compose it can be seen as accessories and pipes. The resulting drawings and diagrams are generated in the same software, the programming is carried out in the LabVIEW software which generates the HMI interface for the manipulation of the valves to visualize the air pressure drops when passing through different paths of pipes and accessories. This bench allows you to measure and control operating variables, such as flow and pressure. The design of the different trajectories agrees with the reality of the instrumentation and accessories used in the industry. In conclusion, the new design of the virtual laboratory incorporates materials such as copper, steel and PVC, air as a working substance, as well as straight and curved trajectories, which allow further studies on pressure losses in the pipeline, where the variation of the flow velocity is visualized, this study is complemented with the formulation of the practices in the test bench, thereby improving the understanding of the studied concepts, which indicate a partial solution to the development of physical laboratories, which does not They are available at the Universidad Antonio Nariño, Neiva headquarters